MORAL VALUES IN ROALD DAHL’S NOVEL DANNY, THE CHAMPION OF THE WORLD - Andrian Nasser; Muhammad Fatih Suhadi (JOURNAL OF LANGUAGE, 2022)
The research,  aiming  to analyze the forms of moral values in Danny, the Champion of the World novel,  is supported by respective theory proposed by  Schwartz and Boehnke. The writers use descriptive qualitative method to identify and analyze moral values of the characters in the novel. Moral is related to the differences between right or wrong behaviors  to be adjusted to standard manners in social life. Value is a core of social standard held by an individual or a group. Moral values are defined as guidelines that assist a person to decide something to be right or wrong.The moral values which are analyzed in this study are honesty, responsibility, modesty, and bravery. Honesty means one explains how a situation really happens. Responsibility is an obligation of an individual to perform the duty or task assigned. Modesty is quality of not being too proud or confident about oneself or one’s abilities. Bravery is having the courage to stand out in any situation based on the principle of truth. The results show  that the major characters in the novel show their moral values in the whole course of the plot.